Reconfigurations of the Nymph-Shepherdess and the Cruel Fairy in Contemporary Spanish Poetry: A Fantastic Rewriting in La acacia, by Antonio Gala (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
This paper analyzes the reconfiguration of two characters from western tradition in Antonio Gala’s La acacia. On the one hand, the nymph-shepherdess is studied, coming from the Romanic poetic tradition in general and the Spanish one in particular. On the other hand, the cruel fairy is studied, coming from European poetry in general and the English one in particular. In the first case, we start from the volume prepared by José Lara Garrido (2020) to detect, in poem number 2 of La acacia, most of the characteristics he theorized. In the second case, this same text is compared with the ballad “La belle dame sans merci” (1819), by the English romantic poet John Keats. Thus, this work is inserted within the field of studies concerning the relationships between tradition and modernity in contemporary Spanish poetry, considering the wide network of intertextual connections offered by Gala’s poetry and the rewritings of the fantastic canon.
Keywords: tradition and modernity; nymph-shepherdess; cruel fairy; “La belle dame sans merci”; John Keats; La acacia; Antonio Gala